2015
DOI: 10.1007/s10695-015-0170-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on respiratory burst, oxidative damage and SERPINH1 (HSP47) mRNA expression in rainbow trout Oncorhynchus mykiss

Abstract: For rainbow trout Oncorhynchus mykiss, high temperature is a major abiotic stress that limits its growth and productivity. In this study, spleen macrophage respiratory burst (RB), serum superoxide dismutase (SOD), serum malondialdehyde (MDA) and mRNA expression of the SERPINH1 (HSP47) gene in different tissues (liver, spleen, head kidney and heart) were measured in unstressed (18 °C) and heat-stressed (25 °C) fish. Spleen macrophage RB activity, serum SOD activity and MDA content all increased significantly (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…; Wang et al . ). These situations can lead to a stress condition for the trout affecting its immune response (Purcell et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Wang et al . ). These situations can lead to a stress condition for the trout affecting its immune response (Purcell et al .…”
Section: Resultsmentioning
confidence: 97%
“…Water temperature at which lactococcosis occurs is within the optimal range of temperature for rainbow trout, and therefore, it is not likely it can assert any effect in the normal function of the immune system of trout that could explain the onset of the lactococcosis outbreaks (Selong et al 2001;Nikoskelainen, Bylund & Lilius 2004). Nevertheless, the water temperature can also affect the fish metabolism rate and the quality of other parameters in the water, such as oxygen availability Wang et al 2016). These situations can lead to a stress condition for the trout affecting its immune response (Purcell et al 2016) and therefore increasing its susceptibility to infection.…”
Section: Immunoproteome Analysis/immunoblot Analysis Of L Garvieae Pmentioning
confidence: 99%
“…SERPINH1 is a well-established heat inducible protein and its synthesis increases strongly under heat-shock conditions, being regulated by a heat shock element in its promoter region; constitutive and tissue-specific expression of SERPINH1 correlates with that of collagen and is regulated via enhancer elements located in the promoter and intron regions [ 42 ]. SERPINH1 has been reported to be strongly induced following exposure to chronic thermal stress in multiple fish species, including O. nerka [ 9 , 30 ], O. gorbuscha [ 9 ], O. mykiss [ 6 , 7 , 45 ], O. tshawytscha [ 17 ], Hypomesus transpacificus [ 16 ], Gadus morhua [ 46 ], Pomacentrus moluccensis [ 47 ], and Puntius sophore [ 48 ]. Our thorough literature review showed that SERPINH1 has not been recognised as an upregulated gene in response to any other stressors in fish, although in mammals it is also associated with fibrosis in response to parasite infections [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental temperatures have extensive biological implications for all organisms, but ectotherms in aquatic systems are particularly affected by thermal profiles and climate regimes in terms of their distribution, physiology and behaviour [ 5 ]. Temperature has a fundamental impact on the physiology and biochemistry of individuals, especially ectothermic fish that inhabit thermally variable environments [ 6 , 7 ]. Increases in water temperature can occur due to a variety of natural and anthropogenic causes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serpin H1 binds very speci cally to collagens and procollagens to facilitate their assembly and stabilization and plays an important role in collagen biosynthesis [90]. Moreover, Serpin H1 is involved in the breakdown of reactive oxygen species (ROS) produced during oxygen stress as recently shown in rainbow trout (Oncorhynchus mykiss) [91]. Hence, the increased expression of serpinh1 mRNA in the liver may have assisted in the stabilization of collagen molecules within the extracellular matrix (ECM), and further enabled the elimination of generated ROS to maintain cellular homeostasis during this thermal challenge.…”
Section: Heat Shock Response Unfolded Protein Response and Endoplasmmentioning
confidence: 99%